Carson mango-soft candy TM a business plan for small scale production of soft candy - Cariño, Carene Mae S. (2010)
Carson Foods Manufacturing Company is classified as a Small-Scale Business based on its number of employees and production. The company is owned by Ms. Carene Mae S. Cariño and its main product is mango-sago soft candy. Candies are known for its sweet characteristic because of its sugar and other ingredients. Some people are limited to eat cndy because it can cause them diabetes or even obesity. However Carson Mango-Sago Soft Candy offers a sweet and delicious candy that is rich in fiber, anti-oxidants and vitamins. People can now enjoy a tasty candy with multiple health benefits. The candies are individually wrapped, and the mango flavor provides the rich, lightly sweet fruity taste. They are little less dense than the standard gummy candies, and their flavor is natural and delicious. On the other hand, the sago supplements, the dietary fiber, protein, calcium, iron, carotene, thiamine, and ascorbic acid contents of the product make the candy healthy. Thus, the target market of the business are those people who love to eat candy and are health conscious. A pack of Carson Mango-Sago Soft Candy contains 20 pieces of individually wrapped candies, each weighing approximately 50 grams. A pack costs Php18.00 only which is very affordable as it packages a delicious and healthy benefit in a candy. The company will exist to satisfy the costumers? cravings of sweet and natural flavoured candies, and to provide an affordable but delicious product to our valued customers. The most important factor of the business will be the customer. Thus, the Company will constantly respond to the desire of the consumers and will see to it that their money spent for the product is worthwhile. The company will keep on developing new products to get on the market. Promotion will be continuous so that the consumers are updated with the product. These strategies are expected to keep the business going